The ersatz elevator - Snicket, Lemony; Helquist, Brett (London : Egmont Books, 2002)
The woeful saga of the Baudelaire orphans continues as evil Count Olaf discovers their whereabouts at Esmé Squalor's seventy-one bedroom penthouse and concocts a new plan for stealing their family fortune.
Includes audiobook.
Keywords: Humorous fiction; Orphans -- Fiction